Pemanfaatan Komposit Biosorben Tanah Liat dan Arang Bambu dalam Mengurangi Kandungan Zat Warna pada Limbah Cair Industri Batik - Tamyiz, Muchammad; Hidayah, Natasya Nur; Salsabella, Aulianita; Maulidiyah, Takrimatul (Universitas Diponegoro, 2019)
The batik industry in Indonesia is one of the small and medium business sectors (SMEs) which is a source of work for some people. The batik industry produces various kinds of liquid waste, one of which is dyes including remazol dyes. In this research, clay and bamboo charcoal which are activated by HCl 1 M were made into a composite biosorbent with a ratio of clay and bamboo charcoal (80%: 20%). In this study, two variables are used, namely dose and contact time variation. The results of removal efficiency for variable adsorbent doses and contact time respectively were 30.00% and 31.33%. FTIR spectrum analysis shows wave numbers 1338.64 and 1309.71 cm-1 which is the C-H bending region. The peak at wave number 1539.25 cm-1 with strong and tapered absorption is identified as aliphatic C-C strains which are functional groups of activated charcoal. The spectrum gives a clay-charcoal composite specification when the absorption peak at wave number 3462.34 cm-1 there is an interaction between O-H in clay and O-H in charcoal, causing an increase in absorption intensity. The use of clay and bamboo charcoal biosorbent can reduce levels of dyes in batik industry liquid waste.